Regulation of Anti-Oxidative, Anti-Inflammatory, and Anti-Apoptotic Activity of Advanced Cooling Composition (ACC) in UVB-Irradiated Human HaCaT Keratinocytes - Jungha Park (International Journal of Molecular Sciences, 2020)
We recently demonstrated that advanced cooling composition (ACC) has effective ingredients that exhibit anti-inflammatory effects in RAW 264.7 cells stimulated with lipopolysaccharide (LPS) and exhibit strong antimicrobial effects on Pseudomonas aeruginosa, Staphylococcus aureus, MRSA (methicillin-resistant Staphylococcus aureus), Candida albicans, and Streptococcus mutans. To further investigate whether ACC has beneficial effects in ultraviolet B (UVB)-irradiated human keratinocytes (HaCaT cells), HaCaT cells were pretreated with ACC prior to UVB irradiation. Our data showed that ACC, which is effective at 100 µg/mL, is nontoxic and has an antioxidative effect against UVB-induced intracellular reactive oxygen species (ROS) in HaCaT cells. In addition, ACC exerts cytoprotective effects against UVB-induced cytotoxicity in HaCaT cells by inhibiting abnormal inflammation and apoptosis through the regulation of mitogen-activated protein kinase (MAPK) signals, such as jun-amino-terminal kinase (JNK), p38, and extracellular signal-regulated kinase (ERK). Therefore, these results indicate that ACC is a potentially beneficial raw material that possesses antioxidative, anti-inflammatory, and antiapoptotic effects against UVB-induced keratinocytes and may have applications in skin health.